Whiteness, populism and the racialisation of the working class in the United Kingdom and the United States. Issue 5 (3rd September 2019) - Mondon, Aurelien; Winter, Aaron
ABSTRACT: The election of Donald Trump and the Brexit vote were widely hailed as examples of (white) working class revolts. This article examines the populist racialisation of the working class as white and 'left behind', and representative of the 'people' or 'demos', in the campaigns and commentaries. We argue that such constructions made race central, obscured the class make-up, allowed for the re-assertion of white identity as a legitimate political category and legitimised, mainstreamed and normalised racism and the far right. Moreover, it delegitimised Black, Minority Ethnic and immigrant experiences and interests, including working class ones. We show that the construction of the votes as (white) working class revolts, and representing the 'people' and/or 'demos', is based on a partial reading of electoral data, misrepresents the votes, stigmatises the working class, and supports an ideological purpose which maintains the racial, political and economic status quo.